Compassion Fatigue, Burnout, and Psychological Flexibility among Healthcare Workers : Emotional strain in Sarawak tertiary hospitals - Ling Choo, Chiew; Yoke Yong, Chen; Mohamad Adam, Bujang; Keng Sheng, Chew; Md Mizanur, Rahman; Rekaya Vincent, Balang; Siok Ping, Voon; Raveca, Ridi (e-International Publishing House, Ltd., UK, 2025)
This cross-sectional study investigated the relationships between Compassion Fatigue (CF), Burnout (BO), and Psychological-Flexibility (PF) among Healthcare Workers (HCWs) in Sarawak government hospitals. Results showed that 45.7% of HCWs experienced CF, while 52.4% reported personal burnout (PB), 17.8% work-related burnout (WB), and 10.9% client-related burnout (CB). The mean PF score was 81.7 (SD = 16.3). Multivariate analysis revealed significant associations between gender and CF (p < .001), marital status and PB (p = .046), then work-position and CB (p = .025), suggesting that sociodemographic factors significantly influence occupational stress. These findings highlight the need for targeted interventions support HCWs well-being.